PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP HASIL BELAJAR SERVIS BAWAH BOLAVOLI (STUDI PADA SISWA KELAS VIII SMP NEGERI 2 NGRAYUN, PONOROGO) - YUDHIANTO, ARINDRA (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Volleyball game is a complex game that could not be easlly done by everyone. In volleyball learning the basic and advanced techniques is required to play volleyball well and effectively. One of the basic technique used is volleyball under service that is the first movement made by a volleyball player. Formulation of the problem posed in this research is whether there is any influence of STAD cooperative learning model and how big is the influence. The purpose of this research is to find out the effort of Student Teams Achievement Division (STAD) cooperative learning model application to the learning outcome of the volleyball under service in the eighth grade students of SMP Negeri 2 Ngrayun, Ponorogo. STAD cooperative learning model is one approach in learning that emphasizes student engagement ful in a group, both physical and mentally and students as subjects in every learning process. With the implementation of STAD cooperative learning, the veceacher hopes to increase to the outcome of learning of volleyball under service. This research was a descriptive quantitative with experimental approach. The sample in this research amounted to 66 students, which consists of 34 students from 8A class as the experimental group and 32 students from 8D as the control group. From the calculation using independent t test can be conclused that there are significant influence of Student Teams Achievement Division (STAD) cooperative learning model to the outcomes volleyball of under service, as evidenced by the results t count is 1,753 greater than t table (1,753> I,664) with significant level 0,05. The value of influence Student Teams Achievement Division (STAD) cooperative learning model to the outcomes learning of the volleyball under service to the eighth grade students of SMP Negeri 2 Ngrayun is 17,55%. Keywords: Type STAD cooperative learning, under service volleyball, outcomes learning.